Reflection of Humanistic Value in English Textbook: English Skills Perspective - Sri Arfani; Juhana Juhana; Nur Qalbi (Al-Ishlah: Jurnal Pendidikan, 2021)
The study purpose was to find out humanistic values in English textbooks through English skills perspective. A good textbook has to have an impact on students’ attitudes. The method used content analysis. The data is taken from discourse text, namely monologue, dialogue, and exercise. Two books were used for grades VII, VIII, and IX in Junior High School South Jakarta. The findings showed that each language skill in the English textbook has humanistic values with various types that refer to the value of character education. Listening skills have three values, namely 1) Freedom values are religion, independence, hard work. 2) Optimistic values are creativity, discipline, and curiosity. 3) Social values are caring for the environment and cooperation. Speaking skills has five values, namely 1) Freedom values are religion, independence, hard work. 2) Equation values are democratic and empathy. 3) Brotherhood values are friendly, responsible, and respectful respect. 4) Optimistic values are discipline and curiosity. 5) Social value is cooperation. Reading skills has three values, namely 1) the value of freedom is religion and independence. 2) The equality value are democratic and empathy. 3) Brotherhood values are friendly and responsible. 4) Optimistic values are discipline, respectively, creativity, and curiosity. 5) Social value is cooperation. Writing skills have three values, namely  1) the value of freedom is religion and independence. 2) Optimistic values are creative, and curiosity. 3) The social values are environmental, peace, love, patriotism or nationalism, and cooperation. English textbooks have human values for each English skill exposed to various values relevant to character values. Each humanistic value implies changes in student attitudes, both about the learning process and social life.